Addressing platform power: The politics of competition policy. (1st November 2020) - Popiel, Pawel
Digital platforms elude legal and regulatory frameworks traditionally used to address market power, speech and disinformation issues. One of the dominant policy responses to addressing these issues involves reforming competition policy to better manage digital platform markets. This case study examines how stakeholders, including tech giants, their competitors, regulators and advocacy groups, deploy competition policy to address platform power in a series of 2019–20 US congressional hearings on the subject, with implications for the wider global debate. The article traces the politics underlying these debates, which manifests in variations in stakeholders' definitions of platform power and their proposed solutions, reflecting tensions over the role of the state in managing markets and in addressing non-economic concerns associated with digital platforms. The article concludes with a consideration of what this politics implies for policy interventions aimed at addressing platform power.